Análisis del comportamiento del esfuerzo desviador y módulo elástico a través del ensayo triaxial tipo uu no saturado en Cangahuas de la parroquia Quisapincha - Manotoa Guachamboza Darwin Marcelo (2026)
The purpose of this research is to analyze the deviator stress and elastic modulus behavior in cangahua-type soils from the Quisapincha parish, through the execution of the unconsolidated unsaturated triaxial (UU) test, following ASTM D2850 and AASHTO T234 standards. Ten undisturbed samples were extracted from test pits, preserving their natural characteristics according to INEN 687 and ASTM D7015 standards. Each sample was subjected to tests for moisture content, particle size distribution, Atterberg limits, and classification according to the Unified Soil Classification System (USCS) and AASHTO. The results determined that they are ML type soils (low plasticity silts), with percentages retained on the #200 sieve less than 50%, and SM type soils (silty sands), with percentages of fines retained on the #200 sieve greater than 50%. Moisture contents ranged from 3.5% to 12.2%, reflecting different natural saturation conditions. UU triaxial tests allowed for the determination of maximum deviator stresses, which exhibited an increasing behavior with respect to the applied confining stress (50, 100, and 200 kPa). The values ranged approximately from 337 kPa to 1360 kPa, demonstrating variations associated with the moisture content and internal structure of the cangahua soil. The shear strength parameters obtained show internal friction angles between 26.88° and 36.61°, falling within or slightly above the ranges reported by other authors for cangahua soil. Cohesion showed significant variability, with values between 55 kPa and 240 kPa, demonstrating that the soil's strength depends strongly on its natural state and degree of weathering. The secant elastic modulus (E50) yielded values ranging from 16,593 kPa to 79,391 kPa, establishing that the material's stiffness varies considerably among samples, being greater in those with lower moisture content and a more compact structure. The overall results confirm that the cangahua-type soil of Quisapincha exhibits low plasticity, considerable strength in a dry state, and a marked loss of strength with increasing moisture content, making it a geotechnically sensitive material. The study provides reliable mechanical parameters for foundation design in the parish, contributing fundamental data for future research and improving building planning in areas with high seismic risk.